Transaction services and SME internationalization: The effect of home and host country bank relationships on international investment and growth. Issue 1 (February 2017) - Eriksson, Kent; Fjeldstad, Øystein; Jonsson, Sara
Highlights: Builds on the argument that the transaction sector enables economic growth. Investigates effects of SMEs' bank relationships on specific investments and growth. Finds that host and home country banks affect the dependent variables differently. Contributes by explicating the role of banks in international business relationships. Abstract: Building on the argument put forward byNorth and Wallis (1994) that the transaction sector enables economic growth by lowering the costs of transacting, we investigate how internationalizing firms' host and home country bank relationships affect their international specific investments and growth. Banks provide payment, liquidity, and risk management services, which are essential to international business relationships, yet little is known about how banks affect international business relationships. In a sample of 255 small and medium-sized enterprises (SMEs), we find that host and home country bank relationships affect the dependent variables differently. We contribute to the literature by explicating the role and effects of banks in international business relationships. Our findings have implications for understanding transaction services in international business as well as the choices made by their customers.